GLOBAL GOVERNANCE AND THE STATE: ASSESING THE ROLE OF THE STATE IN GLOBALISATION - Aryanta Nugraha (Jurusan Ilmu Hubungan Internasional, 2010)
Global governance is seen as a new mechanism to manage global neighbourhood and to mitigate global problems by involving all stake holders (states and non-states actors) of global politics. One of the key questions that has been debated is whether global governance challenges the sovereignty of the state. This paper is trying to explore the impact of global governance on the role of the state. It argues that the force of globalisation pushes the states to reconfigure their national policy autonomy and enhance capacity to promote domestic interest. The state power is not completely in decline but it is reconfigured toward different role that match to globalization challenge toward a new role as a regulatory power. Keywords: global governance, state